Petrography and geochemistry of precambrian ultramafic, mafic and felsic meta-igneous rocks within the Republic of Congo - Plavy Ntsiele, Legran Juldit Espoir (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2023.